O Estado em Benjamin Constant: seu fundamento na história da igualdade - Gabriel Afonso Campos (2021)
The work intends to demonstrate that there is a centrality of the value of equality in the Philosophy of Henri-Benjamin Constant de Rebecque (1767-1830). It is argued that the sentiment and the idea of equality are foundational to all political and social institutions, including the modern principle of individual liberty. The work is based on the assumption that there is, for Constant, an attribution of meaning to history and an acknowledgment of the historical need for political and social institutions. For Constant, the unfolding of the historical process is the very idea of equality, of which individuals progressively become aware over time. Such idea, shared collectively, is responsible for shaping political and social institutions, giving rise to regimes that gradually approach it, namely, theocracy, civil slavery, feudalism, hereditary nobility and the Rule of Law. Thus, the establishment of State competences, the guarantee of individual rights, the duty to obey the law and political freedom are liberal values which, although defended by Constant as essential in Modernity, refer to the idea of equality and the history of its realization. The liberalism defended by Constant, therefore, has a foundation in the history of equality, and not in contractual or natural law assumptions.